Pengaruh Religiusitas, Literasi Zakat, dan Kepercayaan (Trust) terhadap Minat Muslim Generasi Z dalam Membayar Zakat Digital - Rabi’ah Maharani Putri; Dika Jatnika (Journal of Islamic Economics and Finance, 2025)
In the digital era, paying zakat has become more convenient through digital platforms such as BAZNAS, Gopay, and OVO. However, this convenience also comes with risks, such as the leakage of personal data, which can affect Generation Z’s interest in paying zakat digitally. Furthermore, zakat literacy in Indonesia remains relatively low. This study aims to analyze the influence of religiosity, zakat literacy, and trust on the interest of Muslim Generation Z in paying digital zakat. A quantitative approach was used with data analysis conducted through Structural Equation Modeling (SEM) using the Partial Least Square (PLS) method via SmartPLS 4.0 software. The results show that religiosity and trust have a significant effect on the intention to pay digital zakat, while zakat literacy does not have a significant impact. These findings imply that zakat institutions should focus on strategies that strengthen trust and religiosity to increase Generation Z’s participation in digital zakat payment.